Effect of UV-Photofunctionalization on Bioactivity of Titanium to Promote Human Mesenchymal Stem Cells - MR Shbahangfar; E Jafari; A Tarashohi; P Olyaee; T Bitaraf (Islamic Azad University, 2019)
Background and Aim: The present study introduces photofunctionalization as a technique for tackling biological aging and increasing the bioactivity of titanium. This in-vitro study evaluated the effects of ultraviolet (UVC) light treatment of titanium surfaces with different time-related changes on the behavior and function of human mesenchymal stem cells (MSCs). Materials and Methods: MSCs were cultured on nine untreated titanium surfaces (four-week-old surfaces; group 1), nine fresh UVC-treated surfaces (immediately after UV treatment; group 2), and nine three-day-old UVC-treated surfaces (group 3). Cellular proliferation and attachment were measured by MTT. Alkaline phosphatase (ALP) was assessed by total protein extraction, and the enzyme activity was evaluated using a special ALP kit. One-way analysis of variance (ANOVA) and post-hoc Tukey's test were used to examine the effect of UVC on titanium surfaces. Results: The mean attachment of MSCs to titanium disks in groups 1 to 3 was 0.118±0.003, 0.103±0.007, and 0.155±0.009, respectively. The mean proliferation of MSCs in groups 1 to 3 was 0.229±0.004, 0.189±0.023, and 0.298±0.020, respectively. The proliferation and attachment in group 3 were significantly higher compared to other groups (P<0.05). Speeds of MSCs growth in groups 1 to 3 were 94%, 81%, and 92%, respectively. The ALP activity of MSCs in groups 1 to 3 was 0.153±0.003, 0.187±0.003, and 0.161±0.003, respectively. The ALP activity in group 2 was significantly higher compared to other groups (P<0.05). Conclusion: UVC pretreatment of titanium surfaces increases the ALP activity. However, cellular attachment and proliferation were not increased in the present study due to the high probability of laboratory error.